Numerical Analysis of the Continuous Composite Slab Strengthened by CFRP Laminate in the Hogging Moment Region - W. Dahham, Khalid; Baharom, Shahrizan; S. Majdub, Mohamed (International Journal of Engineering and Technology, 2019)
In this study, 3-D finite element models were used to investigate the performance of a continuous composite slab (CCS) with profiled steel sheet strengthened by CFRP laminates in a negative moment region. FE models were validated using available experimental data before being used for parametric studies. The parameters were the number of CFRP, slab thickness and concrete strength. The results obtained from the finite element analysis of the strengthened CCS models agreed well with the experimental tests where the deviation in the ultimate hogging moment is only between –2.0% and +3.0%. It proved that the developed FE model is capable of simulating the CCSs strengthened in the hogging region by CFRP laminate. Results have shown that the strengthening of the CCS specimen in the hogging region with CFRP laminates significantly improved its moment capacity about 23% and 91% using one and three CFRP laminate, respectively. Furthermore, increased in slab thickness and concrete strength resulted in higher load improvement.
Keywords: Continuous composite slab; carbon fibre-reinforced polymer; hogging moment.